A. $207.63
B. $310.27
C. $363.82
D. $313.37
3 hours
B.
1 hour
C.
30 hours
D.
20 hours
3y 2 z(2y 2 z + 4yz - y + z)
Answer: 48(y*z)^2 - 6z*y^2 - 6y*z^2
Step-by-step explanation: We want to find the product:
3y*2z*(2y*2z + 4yz - y - z)
First, distribute the product:
3y*2z*2y*2z + 3y*2z*4yz -*3y*2z*y - 3y*2z*z
now, let's simplify the equation:
(3*2*2*2)(y*z)^2 + (3*2*4)(y*z)^2 - (3*2)z*y^2 - (3*2)y*z^2
24(y*z)^2 + 24(y*z)^2 - 6z*y^2 - 6y*z^2
48(y*z)^2 - 6z*y^2 - 6y*z^2
If the equation you want to distribute is:
(3y^2z)*(2y^2z + 4yz - y - z)
the distribution is:
(3y^2z)´*(2y^2z) + (3y^2z)*4yz -(3y^2z)*y - (3y^2z)*z
6y^4z + 12y^(2z + 1)*z - 3y^(3z + 1) - (3y^2z)*z
b. -4 √5i
c. 4 √5i
d. 4 √5
Answer:
Your answer would be c.
Step-by-step explanation:
The value of x in the equation a – bx = cx + d is = a - d / c + b
The value of x in the equation 5 – 6x = 8x + 17 is - 6 / 7
a - bx = cx + d
add bx to both sides of the equation
a - bx + bx = cx + bx + d
a = cx + bx + d
subtract d form both sides of the equation
a - d = cx + bx + d - d
a - d = cx + bx
using distributive law on the right side of the equation
a - d = x (c + b)
divide both sides by (c + b)
Therefore,
x = a - d / c + b
Let's use the same method to solve 5 – 6x = 8x + 17
5 – 6x = 8x + 17
add 6x to both sides
5 – 6x + 6x= 8x + 6x + 17
5 = 14x + 17
subtract 17 from both sides
5 - 17 = 14x + 17 - 17
-12 = 14x
divide both sides by 14
x = -12 / 14
x = - 6 / 7
learn more on equations here: brainly.com/question/7838122